1999
DOI: 10.1007/s003300050910
|View full text |Cite
|
Sign up to set email alerts
|

Digital vs conventional radiography: cost and revenue analysis

Abstract: The objective of this study was to analyse and compare the operating and investment costs of two radiographic systems, a conventional and a digital one, and to evaluate the cost/revenue ratio of the two systems. The radiological activity over 1 year for chest and skeletal exams was evaluated: 13,401 chest and 7,124 skeletal exams were considered. The following parameters of variable costs were evaluated: the difference between variable proportional costs of the two technologies, the effective variable cost of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 1 publication
0
4
0
1
Order By: Relevance
“…Direct digital imaging systems are popular in medical occupations because of their convenience, but many investigations showed that their image resolution is lesser than film‐based radiography (1–4). Some investigators reported little or no significant differences between direct digital (DDR) and conventional radiography (CR) in caries and periapical lesions detection and bone loss estimation (5–9) while in some other reports the differences were obvious (9–16).…”
mentioning
confidence: 99%
“…Direct digital imaging systems are popular in medical occupations because of their convenience, but many investigations showed that their image resolution is lesser than film‐based radiography (1–4). Some investigators reported little or no significant differences between direct digital (DDR) and conventional radiography (CR) in caries and periapical lesions detection and bone loss estimation (5–9) while in some other reports the differences were obvious (9–16).…”
mentioning
confidence: 99%
“…In these studies, parameters such as examination time for digital radiography, manipulation of data at the post-examination period, graphic quality, and number of hourly examinations were investigated. 6 , 7 , 8 , 9 …”
Section: Discussionmentioning
confidence: 99%
“…One study has reported that the cost of the setup of Digital CR is higher than conventional radiography, whereas cost per radiogram is lower with the former. [15] …”
Section: Discussionmentioning
confidence: 99%
“…Pengurangan jumlah film menjadi faktor terbesar dalam mengurangi biaya. Faktor lain berupa berkurangnya pengulangan pemeriksaan yang harus dilakukan, kualitas gambar yang lebih baik, penghematan waktu yang dibutuhkan petugas dalam memproses gambar, dan kemudahan dalam pengarsipan hasil radiografi (Dalla Palma et al, 1999). Potensi meningkatkan efisiensi layanan untuk memangkas sekitar setengah dari besaran biaya total perlu ditelusuri oleh penyedia layanan kesehatan, terutama pada bagian radiologi yang tersebar di banyak fasilitas layanan kesehatan seluruh Indonesia.…”
Section: Pendahuluanunclassified